Exploring the concept of eating dyscontrol in severely obese patients candidate to bariatric surgery. Issue 1 (13th January 2015) - Calderone, A.; Mauri, M.; Calabrò, P. F.; Piaggi, P.; Ceccarini, G.; Lippi, C.; Fierabracci, P.; Landi, A.; Vitti, P.; Santini, F.
Summary Eating dyscontrol constitutes a potential negative predictor for the outcome of treatment strategies for obese patients. The aim of this study was to examine the qualitative characteristics of eating dyscontrol in obese patients who engage in binge eating (BE) compared with those who do not (NBE), and to analyse the relationship between eating dyscontrol and axis‐I, axis‐II, spectrum psychopathology using instruments that explore mood, panic–agoraphobic, social–phobic, obsessive–compulsive and eating disorders spectrum psychopathology (SCI‐MOODS‐SR, SCI‐PAS‐SR, SCI‐SHY‐SR, SCI‐OBS‐SR, SCI‐ABS‐SR). This was a cross‐sectional study involving a clinical sample of adult obese patients with severe obesity (average body mass index = 45 ± 8 kg m−2) and candidate to bariatric surgery who were recruited between November 2001 and November 2010 at the Obesity Center of the Endocrinology Unit, University Hospital of Pisa. All participants completed a face‐to‐face interview, including a diagnostic assessment of axes‐I and II mental disorders (using the Structured Clinical Interview for Manual of Mental Disorders, fourth edition [SCID]‐I and SCID‐II) and filled out self‐report spectrum instruments. Among obese patients not affected by BE, eating dyscontrol was highly represented. Indeed, 39.7% (N = 177) of subjects endorsed six or more items of the Anorexia–Bulimia Spectrum Self‐Report, lifetime version domain exploring this behaviour. The cumulative probability of having axis‐I, axis‐II and a spectrum condition disorder increased significantly with the number of eating dyscontrol items endorsed. In both BE and NBE obese subjects, eating dyscontrol may represent an independent dimension strongly related to the spectrum psychopathology and axes I/II disorders. A systematic screening for eating dyscontrol symptoms by means of self‐report spectrum instruments may be valuable to assign specific treatment strategies.